IMPLEMENTATION OF SIMPLEX METHOD IN OPTIMIZING IRON SALES RESULTS AT BERKAT BANGUNAN SHOPS - Rumetna, Matheus Supriyanto; Lina, Tirsa Nina; Tindage, Jalminj; Ferdinandus, Wiesje (Journal of Computer Science and Technology (JCS-TECH), 2024)
The Blessing Building Shop is an iron sales business located at Klawuyuk Village, East Sorong District, Sorong City, Southwest Papua, 98416. This shop sells various types of iron such as hollow iron, pipe iron and angle iron which are the main products. The problem found at the Berkat Bangunan shop was that the process of picking up the iron was carried out by 2 people, this was because the Berkat Bangunan shop had suppliers from outside the city. Apart from the relatively minimal workforce, sea transportation used to transport iron is also a problem in shipping iron. This research uses the Simplex Method. The aim of using the simplex method is to help iron sellers at the Berkat Bangunan shop in making decisions, making it easier to accurately determine and calculate the maximum profit from iron sales within a period of one week. To simplify the calculation process and obtain maximum results, the calculation process is assisted by using POM-QM for Windows software. The result is that theThank Building Iron Shop earns a maximum profit of IDR 284,642,800 per week